Spending time in the forest or the field: qualitative semi-structured interviews in a randomized controlled cross-over trial with highly sensitive persons - Oomen-Welke, Katja; Hilbich, Tina; Schlachter, Evelyn; Müller, Alexander; Anton, Andreas; Huber, Roman (Frontiers in Psychology, 2023)
The effects of spending time in forests have been subject to investigations in various countries around the world. Qualitative comparisons have been rarely done so far. 16 healthy highly sensitive persons (SV12 score ≥18) aged between 18 and 70 years were randomly assigned to groups spending one hour in the forest and in the field at intervals of one week. Semi-structured interviews were conducted after each intervention and analyzed using a mixed-methods approach of content analysis and grounded theory. Both natural environments induced feelings of inner calmness, inner cleansing, joy, freedom, connectedness, strengthening qualities, and heightened body awareness. The forest environment additionally offered emotional shelter, and showed advantages in promoting inner strength and selfconcentration. People with previous negative experiences in the forest may feel safer in fields because of the wider view and better overview. Important preconditions are enough time and the absence of a judgmental authority. The two environments induced in part different but also similar emotions which might be useful to promote psychological well-being differentially.